2020
DOI: 10.1002/cam4.3376
|View full text |Cite
|
Sign up to set email alerts
|

TERT mutations correlate with higher TMB value and unique tumor microenvironment and may be a potential biomarker for anti‐CTLA4 treatment

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 58 publications
(123 reference statements)
4
38
4
Order By: Relevance
“… 33 A similar association between TERT promoter mutations and higher TMB was recently described in a pan-cancer analysis. 35 The same study also described a longer median OS in a subset of patients with TERT promoter mutations treated with anti-CTLA4 agents. Other genomic biomarkers associated with increased TMB (eg, DNA damage repair gene alterations or the presence of an apolipoprotein B mRNA editing catalytic polypeptide-like (APOBEC) enzyme mutational signature) have been found to predict response to ICI therapy.…”
Section: Discussionmentioning
confidence: 83%
“… 33 A similar association between TERT promoter mutations and higher TMB was recently described in a pan-cancer analysis. 35 The same study also described a longer median OS in a subset of patients with TERT promoter mutations treated with anti-CTLA4 agents. Other genomic biomarkers associated with increased TMB (eg, DNA damage repair gene alterations or the presence of an apolipoprotein B mRNA editing catalytic polypeptide-like (APOBEC) enzyme mutational signature) have been found to predict response to ICI therapy.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, it is very important to select appropriate patients with PDL1 expression high. In addition, it has been reported that some specific gene mutations may have an intimate relationship with the efficacy of immunotherapy [11,[17][18][19][20]. In our study, we first clarify the relationship between PDL1 expression and specific gene mutation types; then, we analyze the relationship between these gene mutation types and survival among patients receiving atezolizumab; importantly, we found that PDL1 high expression without TP53, KEAP1 and EPHA5 mutations could better predict survival for NSCLC patients receiving atezolizumab.…”
Section: Discussionmentioning
confidence: 82%
“…Tumors from both responders and nonresponders had single nucleotide variants in these genes, and we found no clear correlation between the number or types of genes mutated and response to therapy (Supplementary Figure S5). Notably, Li et al recently identified an association between a higher TMB and TERT mutations, conferring an improved prognosis in patients with metastatic melanoma receiving CTLA-4 blockade, and thus, for combined targeting of telomerase and CTLA-4 in these patients (29).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, Li et al. recently identified an association between a higher TMB and TERT mutations, conferring an improved prognosis in patients with metastatic melanoma receiving CTLA-4 blockade, and thus, for combined targeting of telomerase and CTLA-4 in these patients ( 29 ).…”
Section: Discussionmentioning
confidence: 99%